Persepsi Masyarakat Tentang Tempat Penampungan Sementara (TPS) di Kecamatan Lubuk Basung - Safirman Safirman; Dasrizal Dasrizal; Nefilinda Nefilinda (Departement of Mathematics Education, 2023)
This study aims to obtain data, process, analyze and discuss Community Perceptions of Temporary Shelters (TPS) in Lubuk Basung District seen from: 1). Public knowledge about temporary shelters (TPS) in Lubuk Basung District, 2). Public awareness in disposing of garbage in temporary shelters (TPS) in Kec. Lubuk Basung, 3). Level of public education in utilizing temporary shelters (TPS) in Kec. Lubuk Basung.This type of research is descriptive and qualitative research. The population in this study is the entire community in the TPS area, totaling 100 families. The sampling technique is in research using the slovin technique, so the samples taken from the slovin technique are between 10% -20% of the research population. So the sample that is the respondent is 100 families from all residents in Lubuk Basung District. This research instrument uses a questionnaire. .For data analysis using descriptive and qualitative analysis.This study shows that there are: 1). Public knowledge about temporary shelters (TPS) of 61% is categorized as good. garbage in the environment around TPS, 2) Community awareness in disposing of waste in temporary shelters (TPS) of 36% is categorized as not good, this is in accordance with the results of questionnaires and interviews, it is proven that there is still visible garbage scattered around TPS and the community does not sort and choosing when to dispose of garbage to TPS, 3) The level of public education in utilizing temporary shelters (TPS) 51% is categorized as quite good. This is in accordance with the results of the questionnaire and the results of the interviews which proved the level of education in the people of Lubuk Basung District, where the average high school graduate and the environmental conditions around the TPS were starting to get cleaner.